Development of conducting basalt fibre with polymer-based nanocomposite sizing. (June 2020) - Miao, Yu-Chen; Xing, Dan; Xi, Xiong-Yu; Yue, Xiu; Bai, Yong-Xiao; Ma, Peng-Cheng
Highlights: Nanocomposite sizing consisting of carbon nanotubes and epoxy was developed. Full-scale experiments were used to determine the optimal formulation of sizing. The nanocomposite sizing turned the insulating basalt fibre into the conducing one. The mechanism behind the changed electrical property of basalt fibre was studied. The tensile strength of the sized basalt fibre was also significant increased. Abstract: In this paper, polymer nanocomposites made from epoxy and carbon nanotubes were developed and used as a sizing for basalt fibre. Full-scale experiment (two-factor and four-level combination) with quantitative analysis on the stability, wettability, conductivity, and morphology of liquid was applied to obtain the optimum formulation of sizing. The surface, electrical and mechanical properties of basalt fibre before and after sizing were studied. The results showed that nanocomposite sizing was deposited on the fibre surface during the fibre spinning process. The sizing gave significant increases on the electrical and tensile strength of basalt fibre, revealing the effectiveness of nanocomposites as a multi-functional material. The application of conducting sizing was a simple and effective way to enhance the technique value of insulating basalt fibre.